Stability analysis method of high-speed milling considering feed rate influence - HAN Chentong; GUO Miaoxian; JIANG Xiaohui; WEI Shouheng; LUO Shijin (Jixie qiangdu)
High-speed machining technology by improving the cutting speed and feed rate to improve the material cutting rate, machining accuracy and machining quality, is one of the main ways of modern processing. Therefore, to ensure the stability of high-speed machining is the basis of application of high-speed machining. Firstly, based on the traditional stability analysis, the influence of feed rate on the static cutting thickness was further considered, the stability model related to feed rate and radial cutting depth ratio of tool was established, and the stability of high-speed milling was analyzed by combining stability variance ratio. Secondly, based on the single factor variable feed rate test, a filter was designed to filter the frequency component of the spindle speed. The variance ratio between the filtered signal sequence and the original signal sequence was used to analyze the milling stability changes of the continuous variable axial depth test, and the validity of the analysis method considering the feed rate to affect the stability of high-speed milling was verified. The results show that the proposed method can determine milling stability more accurately for high-speed machining with small radial cutting depth. And the axial cutting depth of unstable cutting limit changes slightly with the increase of feed rate, and the feed rate will aggravate the instability of milling system.